(untitled) (Research, Society and Development, 2022)
Staphylococcus spp. have been described as routine members of the human microbiota on the surface of wetter regions of the body, while some species and subspecies have a predilection for the urogenital region. They are also considered opportunistic and have often been a cause of infection in patients with compromised immune systems or using invasive devices in hospitalized patients. However, in recent years, these strains have spread through the community, which could possibly be related to selective pressure due to inappropriate use of antibiotics. Infections caused by Staphylococcus spp. resistant methicillin has caused serious problems inside and outside the hospital setting. Within the community, it causes colonization of people, increasing the chance of death in all sexes and age groups and in pregnant women they have been considered important sources of pathogenic microorganisms due to the virulence factors presented by this bacterium and the physiological and anatomical conditions of the pregnant woman, becoming, thus, a threat of propagation of infections by multidrug-resistant strains.